AN INVESTIGATION OF THE APPLICATION OF SERVQUAL IN THE ENHANCEMENT OF SERVICE QUALITY AMONG INTERNATIONAL POST- GRADUATE STUDENTS: COMPARING INDONESIA WITH MALAYSIA - Sandra Sunanto; Ria Satyarini; Taufiqurrahman Taufiqurrahman; Amran Amran; Ahmadreza Shekarchizadeh (Research Report - Humanities and Social Science, 2010)
Universities strive to deliver high-quality service throughout its educational curriculum and its administrative process. In order to do so, universities must view students as their primary clients and seek to maximize their satisfaction with the level of university offered.Using SERVQUAL model, this research has an objective to investigate the performance of services delivered by universities to the international post-graduate students Indonesia. As part of joint research commitment with Malaysian scholars, findings of this research will be compared with their findings.This research uses paired T-test sample and regression analysis to test the hypotheses. Students did not too satisfy with the performance of non-faculty staff but they were quite satisfied with general and faculty performances.However, universities still have to improve their performances in order to deliver service excellences to their students.Keywords: Education, SERVQUAL, Service Excellences, Satisfaction.